Quality of Life and Volume Reduction in Women with Secondary Lymphoedema Related to Breast Cancer - Marcus Lanza; Anke Bergmann; Maria Giseli da Costa Leite Ferreira; Suzana Sales de Aguiar; Ricardo de Almeida Dias; Karen de Souza Abrahão; Ester M. Paltrinieri; Ruy G. Martínez Allende; Mauro Figueiredo Carvalho de Andrade (International Journal of Breast Cancer)
Purpose. To assess the quality of life (QOL) as a predictor of volume reduction in women undergoing complex physical therapy (CPT) for lymphoedema following breast cancer. Methods. Clinical trial in 57 women undergoing CPT. Results. At baseline, in measuring quality of life for the EORTC QLQ-C30 questionnaire subscale of functionality, the worst scores for emotional function (55 points) and better social function (89 points) were observed. The symptom scales showed the worst pain averaged (66 points). The overall quality of life showed a low score (40 points). In the BR 23 module, low scores were observed in the field of future perspective (47 points). After treatment of lymphoedema, absolute reduction of excess volume between the upper limbs of 282 mL was observed, representing a reduction of 15%. No association was observed between the domains of quality of life and response to treatment of lymphoedema. Conclusion. This study included 57 women with advanced and chronic lymphoedema in early treatment with CPT and low scores for quality of life. The lymphoedema therapeutic response was not influenced by the QOL at the beginning of treatment.